ANALYSIS OF THE CLEAN AND HEALTHY LIVING BEHAVIOR ON DIARRHEA INCIDENCE AMONG CHILDREN AGED 6–12 YEARS IN MOROSI HEALTH CENTER : CLEAN AND HEALTHY LIVING BEHAVIOR ON DIARRHEA - Yanti, Fitri; Ferdayanti, Putri; Zuldadlih, La Ode Sahlan (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The Clean and Healthy Living Behavior (CHLB) is important for prevent diarrhea, which is still common in children school. WHO (2024) states diarrhea causes 8% of deaths children in developing countries consequence sanitation bad and low habit hygienic. Research This aim analyze relationship between CHLB and incident diarrhea in children ages 6–12 years in the work area Morosi Community Health Center. Methods: Study This use approach quantitative cross-sectional. Population totaling 902 children, with sample as many as 90 children were taken use Slovin's formula. Data collected through questionnaire closed and inspected water laboratory, including four CHLB variables: washing hand use soap, ownership toilet healthy, clean water provision, and consumption vegetables and fruit. Analysis using the chi-square test and the phi coefficient. Results: The results show all CHLB variables are related significant with incident diarrhea, with strength connection medium: hand washing (φ = 0.346), healthy toilets (φ = 0.517), clean water (φ = 0.544), and consumption of fruits and vegetables (φ = 0.451). Conclusion: In conclusion that behavior hygiene and pattern consumption Healthy lower risk diarrhea. It is recommended existence intervention government, health centers, and parents for push implementation of CHLB consistent.